2015
DOI: 10.1111/imr.12268
|View full text |Cite
|
Sign up to set email alerts
|

Immunoevasion and immunosuppression of the macrophage by Mycobacterium tuberculosis

Abstract: By virtue of their position at the crossroads between the innate and adaptive immune response, macrophages play an essential role in the control of bacterial infections. Paradoxically, macrophages serve as the natural habitat to Mycobacterium tuberculosis (Mtb). Mtb subverts the macrophage's mechanisms of intracellular killing and antigen presentation, leading ultimately to the development of tuberculosis (TB) disease. Here, we describe mechanisms of Mtb uptake by the macrophage and address key macrophage func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
195
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 148 publications
(183 reference statements)
5
195
0
5
Order By: Relevance
“…Successful bacterial pathogens have thus evolved strategies to mask these virulence factors from detection or to blunt the host response that is initiated (72)(73)(74). Indeed, a number of studies in several different systems have revealed that immune sensing of virulence factor activity promotes pathogen clearance (36,(75)(76)(77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
“…Successful bacterial pathogens have thus evolved strategies to mask these virulence factors from detection or to blunt the host response that is initiated (72)(73)(74). Indeed, a number of studies in several different systems have revealed that immune sensing of virulence factor activity promotes pathogen clearance (36,(75)(76)(77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
“…by compromised cell membranes and nuclear envelopes, cytoplasmic swelling and cellular breakdown [22][23][24][25]. The apoptotic death of infected macrophages has been proposed to be one of the main mechanisms by which the organism controls tuberculous infection through depopulating pathogenic microorganisms and infected cells [4][5][7][8][9]25]. By contrast, the necrotic death of infected cells leads to the release of living bacteria into the extracellular environment and further spread of infection throughout animal and human organisms [5,[24][25][26][27][28].…”
mentioning
confidence: 99%
“…By contrast, the necrotic death of infected cells leads to the release of living bacteria into the extracellular environment and further spread of infection throughout animal and human organisms [5,[24][25][26][27][28]. At present, autophagy as a way by which host cells eliminate intracellular pathogens during latent chronic tuberculous infection and at its reactivation is extensively studied [5,8,9,23,24,29,30]. …”
mentioning
confidence: 99%
“…As opposed to necrosis, apoptosis is a 'silent' and tightly regulated form of cell death, where cytoplasmic contents are contained within membrane-bound structures. Phosphatidyl serine on these apoptotic bodies leads to recognition and removal in a process called efferocytosis, exerted by tissue macrophages recruited monocyte-derived macrophages and neutrophils [194]. Thereby, efferocytosis constitutes a second line of defense, limiting tissue damage and inflammation due to apoptotic cells undergoing secondary necrosis.…”
Section: Phagolysosomal Maturation Phagolysosomal Maturation Phagolysmentioning
confidence: 99%
“…Apoptosis is also linked to more efficient antigen presentation [198], a process typically impaired by virulent strains [194], and experimental induction of macrophage apoptosis severely attenuated the viability of intracellular bacteria [199]. This could not be attributed to intrinsic microbicidal activity of apoptotic macrophages, but to efferocytosis by bystander macrophages, resulting in successful lysosomal delivery and degradation of the apoptotic Mtb-containing macrophage [99].…”
Section: Phagolysosomal Maturation Phagolysosomal Maturation Phagolysmentioning
confidence: 99%